Judgement, decision making and success in sport - Bar-Eli, Mikhaʾel; Plessner, Henning; Raab, Markus (W-B series in sport and exercise psychology, 2011)
"Judgment, Decision-Making and Success in Sport introduces the fundamental approaches of Judgment and Decision-Making (JDM) research in psychology and applies them directly to a variety of JDM problems in sport"--